A self-help diet and physical activity intervention with dietetic support for weight management in men treated for prostate cancer: pilot study of the Prostate Cancer Weight Management (PRO-MAN) randomised controlled trial. Issue 5 (14th September 2019) - Mohamad, H.; Ntessalen, M.; Craig, L. C. A.; Clark, J.; Fielding, S.; N'Dow, J.; Heys, S. D.; McNeill, G.
Abstract: Overweight and obesity may increase risk of disease progression in men with prostate cancer, but there have been few studies of weight loss interventions in this patient group. In this study overweight or obese men treated for prostate cancer were randomised to a self-help diet and activity intervention with telephone-based dietitian support or a wait-list mini-intervention group. The intervention group had an initial group meeting, a supporting letter from their urological consultant, three telephone dietitian consultations at 4-week intervals, a pedometer and access to web-based diet and physical activity resources. At 12 weeks, men in both groups were given digital scales for providing follow-up weight measurements, and the wait-list group received a mini-intervention of the supporting letter, a pedometer and access to the web-based resources. Sixty-two men were randomised; fifty-four completed baseline and 12-week measurements, and fifty-one and twenty-seven provided measurements at 6 and 12 months, respectively. In a repeated-measures model, mean difference in weight change between groups (wait-list mini-intervention minus intervention) at 12 weeks was −2·13 (95 % CI −3·44, −0·82) kg ( P = 0·002). At 12 months the corresponding value was −2·43 (95 % CI −4·50, −0·37) kg ( P = 0·022). Mean difference in global quality of life score change between groups at 12 weeks was 12·3 (95 % CI 4·93, 19·7) ( P = 0·002); at 12 months there were no significant differences between groups. Results suggest the potential of self-help diet and physical activity intervention with trained support for modest but sustained weight loss in this patient group.